Role of Digital Health transformation in the health care – patient, clinician, service provider and payer perspective - Pilkiewicz, Michal; Pekurari, Romanca (Archives of Pharmacy, 2022)
As with most industries, digital transformation has become a strategic imperative within healthcare – made even more urgent by the COVID-19 global pandemic. Digital Health – patients’ use of mobile devices, wearables and connected virtual assistants – is booming. In fact, it is becoming integrated into virtually every aspect of healthcare. But what is next? And what will stakeholders need to do to ensure it reaches its full potential? According to the IQVIA Institute, there are currently more than 318,000 health apps to track, measure, access and connect healthcare stakeholders; and over 340 consumer wearable devices currently available, with more than 200 new health apps added to app stores every day. While angel and venture capitalists were once the primary investors in digital health, activity has spread to other sectors, including healthcare payers, medical device, and pharmaceutical companies. The focus is also evolving, pharmaceutical companies are shifting their attention from simply providing drug-specific patient apps to developing digital biomarkers to track patient experience and health outcomes to gain a competitive advantage. Furthermore, continuous developments in technologies are helping pharmaceutical companies dive ever deeper into digital health. Digital healthcare transformation in the health care systems in Europe faced a lot of challenges. There are different European initiatives and regulations supporting patient access to innovative therapies and better treatment. To successfully transform healthcare, there is a need to set a proper country digital health strategy, to change legislative environment, to make an IT & technology infrastructure change.